Floral Medallion on the ceiling of the Mandapa - Temples of India Project Team (Jio Institute, 2024)
Painted floral medallion on the ceiling of the mandapa (pillared hall) of the Adinatha Temple. Compared to other paintings on the ceiling, this is a different pattern of a large medallion. Small floral ornamentation patterns are plenty but large medallions are uncommon.